THE INFLUENCE OF PRODUCT VARIATION AND PACKAGING ON PURCHASE DECISIONS OF KEFIR FERMENTED MILK HOME INDUSTRY AT TASIKMALAYA - lati sari dewi; Asep Saeful Falah (Jurnal Hexagro, 2023)
Kefir Fermentation Milk is a pioneer of packaged healthy drinks trying to carry out a product and packaging variation strategy so that consumers do not run to other brands. This study aimed to determine the effect of Product Variation and Packaging on the Purchase Decision of Kefir Fermentation Milk. The research method used in this study is a descriptive method with a quantitative type. The selected respondent was 86 from 600 population with a non-probability sampling technique to determine the sample based on consumers who coincidentally meet with the researcher can be used as a sample if it is deemed that the person who happened to be met is suitable as data source. The results showed that: 1) Product variation on the purchasing decision of Azet Kefir Milk was good, 2) The effect of Product Packaging on the Purchase Decision of Azet Kefir Milk was good, 3) The results of multiple regression analysis showed that Product Variation (X1) and Product Packaging (X2) has a positive influence on the Purchase Decision variable (Y), namely 0.60 for the Product Variation (X1) and 0.10 for the Product Packaging variable (X2). The multiple correlation coefficient is 0.745, which means it is vital. Furthermore, the coefficient of determination is 0.555. The results of hypothesis testing are Fcount > Ftable of 51.705 > 3.11, there is a simultaneous influence between Product Variation and Product Packaging variables on Purchase Decisions, and the Product Variation (X1) variable is 8,018 with a ttable value of 1,988. So that tcount > ttable or 8.018 > 1.988, and for the Product Packaging variable (X2), it is 9.189 with a t-table value of 1.988. so that tcount > ttable or 9.189 > 1.988, thus H0 is rejected and Ha is accepted, which means that product variations and packaging significantly affect purchasing decisions.